2017
DOI: 10.1002/eco.1859
|View full text |Cite
|
Sign up to set email alerts
|

Environmental watering for vegetation diversity outcomes must account for local canopy conditions

Abstract: Hydrology is widely considered to be the dominant driver of understorey vegetation dynamics in arid and semiarid riparian ecosystems. Consequently, environmental watering is often a key approach to restoring and promoting riparian vegetation diversity. Few studies however have considered the role of local factors, for example, shading or litter accumulation, on vegetation responses to flow and how these may influence the outcomes of watering actions. Knowledge concerning modifying effects of local canopy facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Pre‐existing ecological condition of vegetation has been widely shown to affect responses to flows (e.g. Capon, Balcombe, & McBroom, ; Nagler et al., ; Smith, ), and there are similar findings for fish, in which the abundance and individual condition of the stock influence the magnitude of the responses (King et al., ; Koster et al., ). Lagged responses to eflows due to existing poor ecological condition have been identified as an important issue in many parts of the world (e.g.…”
Section: Factors Limiting Ecological Responses To Flow Restorationmentioning
confidence: 88%
“…Pre‐existing ecological condition of vegetation has been widely shown to affect responses to flows (e.g. Capon, Balcombe, & McBroom, ; Nagler et al., ; Smith, ), and there are similar findings for fish, in which the abundance and individual condition of the stock influence the magnitude of the responses (King et al., ; Koster et al., ). Lagged responses to eflows due to existing poor ecological condition have been identified as an important issue in many parts of the world (e.g.…”
Section: Factors Limiting Ecological Responses To Flow Restorationmentioning
confidence: 88%
“…Riparian vegetation is a critical component of inland riverine landscapes, supporting significant biodiversity and providing a wide range of highly valued ecosystem functions and services (Capon et al, 2013;Mahoney & Rood, 1998). In the northern Murray-Darling Basin, longlived riparian trees (largely E. camaldulensis and E. coolibah) play a disproportionate role in the health of both the flora and fauna that rely on the services provided by these trees, such as shade and litter (Capon, Balcombe, & McBroom, 2017) and a constant source of organic matter to the soil. Hence, the broader implications of both protecting standing trees and influencing the recruitment of seedlings cannot be understated.…”
Section: Discussionmentioning
confidence: 99%
“…However, inundation duration is not the only component required for a fuller understanding of seed germination and vegetation establishment. For example, Capon et al () examined the effects of leaf litter and shade on germination, concluding that they may also be important local factors constraining germination during periods of inundation.…”
Section: Discussionmentioning
confidence: 99%
“…Capon () identified an increase in seedling emergence in a desert floodplain after 4–8 weeks of inundation and an increase in the proportion of annual monocot species. A simulated in‐channel flow event led to more abundant and species‐rich germination from the seed bank of bank top riparian sites from the northern Murray–Darling Basin, in comparison with inundation or non‐inundation (Capon, Balcombe, & McBroom, ). However, the authors also found that the leaf litter and shade present comparable controls on the seed bank material to the simulated hydrological events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation